Dampak Sosial Sedekah Jumat Berkah di Masjid Al Badr Nogosari Boyolali - Thoriq, Jamal; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
This research examines the social impacts that arise from the Friday blessing alms program at the Al Badr Nogosari Mosque. This program is actually commonly implemented in mosques today. Almsgiving has been a popular practice for Muslims from the past until now. However, there is something interesting that the author saw with the distribution of Friday alms at the Al Badr Nogosari Boyolali mosque which may not be found in other mosques. The aim of this research is to find out in more depth about the social impact that arises from the distribution of blessed Friday alms at the Al Badr Mosque in Nogosari Boyolali. descriptive qualitative approach method, type of case study. This type of case study is research that focuses on just one selected problem and wants to be understood in depth, ignoring other incidents. The research results show that Friday blessing alms will have a vertical and horizontal impact. Vertically, the giver of alms will feel directly that he feels close to Allah, close to good and far from evil. Horizontally, he will be close to society and loved by people. The social impact for the recipients of alms benefits is that it will produce happiness hormones (endorphins). People who receive alms are like getting new nutrition from gifts from other people. So that a positive effect appears with enthusiasm for life. Meanwhile, the negative impact for alms recipients is the emergence of a greedy spirit. The emergence of gluttony and covetousness is due to a lack of understanding of the importance of people taking care and restraint in matters of food. It is hoped that the results of this research will be a stepping stone for mosque administrators to provide education for the congregation to be more polite and careful when it comes to food.